Pengaruh Lingkungan Kerja Dan Program Kesejahteraan Karyawan Terhadap Semangat Kerja Pada PT. Happy Puppy Tenggarong - Arman Arman; Nilam Anggar Sari (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2021)
Abstract: The purpose of this study was to determine and analyze the effect of the work environment and employee welfare programs on morale at Happy Puppy Tenggarong both partially and simultaneously. Besides that, to find out the dominant variables in influencing work morale. The analytical tool used in this study is multiple linear regression with the number of respondents in this study amounting to 25. The results showed that the variables of the work environment and employee welfare programs had a simultaneous effect on employee morale. The work environment variable has a partial effect on employee morale at Happy Puppy Tenggarong while the welfare program variable has no effect on employee morale. Thus, it can be concluded that the work environment variable has the most dominant influence on work morale. Keywords: Work Environment, Employee Welfare Program